2019
DOI: 10.5751/es-11118-240405
|View full text |Cite
|
Sign up to set email alerts
|

Exploring natural capital using bibliometrics and social media data

Abstract: Research and interest into natural capital, i.e., the stock of the world's natural resources, is increasing as it links humans with nature within a social-ecological system, contributing to ecosystem sustainability. We collected publication data for 300 natural capital papers to explore academic networks and research trends. We used Twitter to collect 14,193 tweets about natural capital over nine months. Analyzing publication data shows three main research clusters, but few coauthorships between the clusters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The distinction between the terms ecosystem services (flows) and natural capital (stocks) is an important point of clarification in the natural capital concept that is often lost in application [63]. Ecosystem services contribute to human wellbeing and the economy-they are explicitly anthropocentric and dependent on human demand [52]-but are a downstream product of ecosystem functions, produced from natural capital stocks ( Figure 2), and realised through interactions with human and manufactured capital [22,64].…”
Section: Environmental Framings Of the Bioeconomy And Natural Capitalmentioning
confidence: 99%
See 2 more Smart Citations
“…The distinction between the terms ecosystem services (flows) and natural capital (stocks) is an important point of clarification in the natural capital concept that is often lost in application [63]. Ecosystem services contribute to human wellbeing and the economy-they are explicitly anthropocentric and dependent on human demand [52]-but are a downstream product of ecosystem functions, produced from natural capital stocks ( Figure 2), and realised through interactions with human and manufactured capital [22,64].…”
Section: Environmental Framings Of the Bioeconomy And Natural Capitalmentioning
confidence: 99%
“…Research initiatives by organisations such as the Capitals Coalition, The Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES), and TEEB have adopted an international and collaborative approach that reflects how ecosystems transcend national boundaries and are relevant to all disciplines. However, there is evidence to suggest the natural capital concept remains clustered within highly specialised groups, dominated by wealthy, English speaking nations that may limit collaboration and bridging between clusters [63,75].…”
Section: Cornerstone 1: International Collaborations Between Governmementioning
confidence: 99%
See 1 more Smart Citation
“…Most authors, however, have focused exclusively on cultural ecosystem services by mapping and quantifying them using images [ 31 , 32 , 33 , 34 ], and few of them have analysed their social perceptions [ 15 , 35 , 36 ]. With reference to Twitter, several authors have analysed the social perception of natural capital, that is, nature and its ecosystem services and protected areas [ 37 , 38 , 39 ] or people’s emotions [ 40 ], but few have focused exclusively on ecosystem services and specifically cultural services [ 41 , 42 , 43 , 44 ]. The only study that analysed the perception of ecosystem services in a broad sense focused on a specific geographical area, namely the Laurentian Great Lakes [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the empirical evidence found in the literature [ 38 , 39 ], the topic under research and our theories, the respective hypotheses for the research questions were identified: (H1) In the social network, there are good interactions between users and high content sharing. (H2) Most influential users in the network are scientists or researchers.…”
Section: Introductionmentioning
confidence: 99%